Transformer Oil Failure Analysis Based on Dissolved Gas Analysis (DGA) Test Using Breakdown Voltage and Fuzzy Logic Methods - Lubis, Rakhmad Syafutra; Akbar, Muhammad Hafizh; Siregar, Ramdhan Halid; Masri, Masri (Journal of Engineering and Science, 2025)
A common problem that occurs in transformers is failure of the insulating oil. One solution to prevent this disruption is to analyze indications of insulating oil failure. Several previous studies on the analysis of transformer insulating oil failure were based on dissolved gas content tests of transformer oil samples. The research was conducted using several methods in processing dissolved gas test results data, such as the TDCG (Total Dissolved Combustible Gas), Roger's Ratio, and Duval's Triangle methods. In this study, two methods were used for comparison, namely the Breakdown Voltage method and the Fuzzy Logic method. The results obtained show that the condition of the insulating oil using fuzzy logic in the Matlab simulation is in accordance with the condition of the transformer insulating oil based on its breakdown voltage characteristics, namely in a normal state. Meanwhile, gas content that is at a high or very high level has a significant impact on the indication of failure in transformer insulating oil, namely the concentration of TDCG and nitrogen gas content.